Improving In Situ Combustion for Heavy Oil Recovery: Thermal Behavior and Reaction Kinetics of Mn(acac)3 and Mn-TO Catalysts - Younes Djouadi; Mohamed-Said Chemam; Chaima Khelkhal; Olga V. Ostolopovskaya; Mohammed A. Khelkhal; Alexey V. Vakhin (Energies)
In this research work, the catalytic performances of two manganese-based catalysts, manganese (III) acetylacetonate (Mn(acac)3) and manganese tallate (Mn-TO), were studied during the process of Ashalcha heavy oil oxidation under in situ combustion conditions. DSC analysis shows distinct thermal behavior of both ligated catalysts during low- and high-temperature oxidation phases (LTO and HTO); for example, the shifting in peak temperature (Tp) in the HTO at a heating rate of 10 °C/min was reduced by approximately 5.3% for Mn-TO and 2.24% for Mn(acac)3 when compared with uncatalyzed heavy oil. Combined isothermal kinetic analyses using the Friedman and Kissinger–Akahira–Sunose analytic methods have provided insights about activation energies and frequency factors over the whole conversion range, where the catalytic performance of Mn-TO showed low activation energies in both LTO and HTO (Eα of Mn-TO was approximately 13.33% (LTO) and 7.68% (HTO) less than with the heavy oil alone). In addition, calculations of the effective rate constant confirmed the increased oxidation rate trend of both catalysts, with Mn-TO exhibiting the highest values. The findings highlight the potential of these manganese-based catalysts, the Mn-TO catalyst in particular, in optimizing heavy oil oxidation processes. The overall results further contribute to developing more efficient ligand catalyst complexes for sustainable heavy oil recovery while continuously improving their efficient application during in situ combustion in the petroleum industry.